Existence of cryogenic magnetic entropy change in Gd based nanoparticles - Zeleňáková, A.; Hrubovčák, P.; Berkutova, A.; Kapusta, O.; Zeleňák, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Magnetic nanoparticles with average diameter of 5–7 nm were prepared by nanocasting method inside of the pores of periodic silica matrix of SBA15 type. The uniform size of the pores limited the particles’ growth what resulted in formation of nanocomposite consisting of monodisperse nanoparticles of Gd2O3 embedded in amorphous silica matrix. Magnetic properties of the material were examined in magnetic fields up to 5 T and in temperature range 2–52 K. The magnetic entropy change of 29 J/kg⋅K was observed at 2 K for field variation 5 T in the investigated nanocomposite what suggests this material could be feasible for cryomagnetic refrigeration applications.